The Prevalence of Physical Activity and Sedentary Behaviours Relative to Obesity among Adolescents from Al-Ahsa, Saudi Arabia: Rural versus Urban Variations - Anwar A. Al-Nuaim; Yahya Al-Nakeeb; Mark Lyons; Hazzaa M. Al-Hazzaa; Alan Nevill; Peter Collins; Michael J. Duncan (Journal of Nutrition and Metabolism)
Purpose. The aims of this study were to explore the lifestyle of young people living in Al-Ahsa Governorate; to investigate differences due to gender, age, school type, and geographical location. Methods. 1270 volunteered youth (15–19 years) completed a self-report questionnaire that contained 47 items relating to patterns of physical activity (PA), sedentary activity, and eating habits. The questionnaire allows the calculation of total energy expenditure in metabolic equivalent (MET-min) values per week. Results. Significant differences in the PA levels of youth were evident with regard to gender, geographical areas, and type of school. Also, normal weight males reported the highest levels of PA compared to overweight and obese. Conclusions. Youth living in rural desert were less physically active than those living in urban or rural farm environments. Youth of “normal” weight were more active than obese. Males were more active than females and PA levels appeared to decline with age.